MEASURES TO INCREASE LIFETIME OF PERICLASE-CARBONACEOUS PRODUCTS IN WORKING LINING OF STEEL-POURING LADLES AT JSC «BSW – MANAGEMENT COMPANY OF HOLDING «BMC» - I. A. Bondarenko; A. K. Turygin; A. L. Artamoshin; A. V. Vengura (Литьë и металлургия, 2016)
A number of actions were carried out during the operation the steel-pouring ladles with working lining of periclasecarbonaceous products, directed on increase of lifetime of industrially used products and on selection of alternative suppliers of these refractory materials.